Entrepreneurial Change In Social Responsibility - Ahmad Al Fahad; Majdi Anwar Quttainah (AIBPM Publisher, 2018)
When it comes to social responsibility nowadays we find a wide variance between what corporations are offering and what should be offered in order to accommodate to what social responsibility is based on. Firstly, let us define corporate social responsibility, CSR is basically a corporation's initiatives to assess and take responsibility for the firm's effects on environmental and social wellbeing. Regardless any assessments regulated by the government. But the question remains, is what corporations doing regarding CSR considered a real social responsibility initiative? In most cases we find that corporations are adopting charities to exploit it as an advertisement and pursue a good image. But for educated people, they can differentiate between a real social responsibility and a false one. “There is nothing wrong about being wrong. But there is a shame of being wrong and doing nothingabout it”. We can never claim that humanity have reached its optimum level of education, morality or sense. In matter of fact, we should acknowledge that the life cycle will keep teaching us a day after one. But one of the most obstacles that faces people with change is a resistance toward a change. And that’s a human instinct to resist a change, and in such a case we shall adapt all methodologies of persuasion, negotiation and bargaining in order to take life, education and science to the next level and create a new generation that thinks differently. As someone unknown said“to sustain a planned change, there is no way better than creating a country inside an existing one then proceed as a snake which changes its own skin” Here where exactly Student’s Solid Stocks (SSS) comes to perform the magic. SSS is an organization that shall be funded by the government to organize, observe and utilize a major method for implementing a real social responsibility for corporations. For now, we’ll concentrate on the main function which is allowing corporations to share a bit of their fixed operating costs with the community (students). In return, a bit of the profits shall be dividends to the students. Yet, this is a very abstracted idea towards what I aiming for. Further information will be found in the following attached slides. Keywords: Corporate social responsibility, workforce planning, venture capitalism, change.